Konflik dan Perubahan Kebijakan di Pegunungan Karst Kendeng: Narasi Belief System dalam Advocacy Coalitioan Framework - Catur Wulandari; Arif Budy Pratama; Hartuti Purnaweni; Kismartini Kismartini (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
This paper aims to investigate the dynamic of environmental policy making in the effort of attaining sustainable development. Using Advocacy Coalition Framework (ACF) as a framework of analysis, our study was conducted in the Kendeng environmental conflict, Rembang Regency. Utilised both primary and secondary data on conflict properties from cement industry’s proponents and opponents, researchers obtained vigorous data and evidence through which the ACF may offer a comprehensive explanation on policy process and change. Finding shows that the coalition of actor has a pivotal role to influence value and behaviour among policy actors in the Kendeng environmental conflict. The result of this study fills the lacuna of research which focuses the main discussion on advocacy coalition actor-based policy analysis. It also offers a policy agenda focusing on the belief system actor-based policy analysis in which Government of Indonesia worth to consider in the policy making process.